2020
DOI: 10.3390/ijms21228723
|View full text |Cite
|
Sign up to set email alerts
|

Large Extracellular Vesicles Can be Characterised by Multiplex Labelling Using Imaging Flow Cytometry

Abstract: Extracellular vesicles (EVs) are heterogeneous in size (30 nm–10 µm), content (lipid, RNA, DNA, protein), and potential function(s). Many isolation techniques routinely discard the large EVs at the early stages of small EV or exosome isolation protocols. We describe here a standardised method to isolate large EVs from medulloblastoma cells and examine EV marker expression and diameter using imaging flow cytometry. Our approach permits the characterisation of each large EVs as an individual event, decorated wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…It is characterized by significantly lower background noise, and it is able to distinguish true single events by imaging objects and excluding convergent events or debris from the analysis. However, just like nanoparticles flow cytometers, imaging flow cytometers are not widely applied and require experience to operate [ 63 , 64 , 65 , 66 ].…”
Section: Methods For the Detection Of Evs From Specific Tissues Ormentioning
confidence: 99%
“…It is characterized by significantly lower background noise, and it is able to distinguish true single events by imaging objects and excluding convergent events or debris from the analysis. However, just like nanoparticles flow cytometers, imaging flow cytometers are not widely applied and require experience to operate [ 63 , 64 , 65 , 66 ].…”
Section: Methods For the Detection Of Evs From Specific Tissues Ormentioning
confidence: 99%
“…A recent finding has demonstrated that the latent membrane protein-1 (LMP-1) is a major viral oncogene expressed in most Epstein-Barr viruses, suggesting a role in packaging and particle secretion by CD63 [65]. Actually, TSG101 and CD9, CD63, LMP-1, CD81, CD82 are used for exosome identification and characterization [1,60,[66][67][68]. In a follow-up, the Syndecan-syntenin-ALIX pathway is a non-ESCRT-mechanism facilitating the ILV formation, exosome-containing syntenin, syndecan, and CD63 are released by heparanase and play a key role in endosomal membrane budding controlled by ARF-6 and PLD-2 [3,57,69].…”
Section: Figurementioning
confidence: 99%
“…By contrast, 5 min exposure to a 645 nm light source released the vast majority (90 ± 5.8%) of Dex that had been loaded into RBCs, consistent with the notion [24] Imaging data was used to calculate the diameter of each cell/event as previously described. [25] Figure 3. Photolysis of Dex-Cbl derivatives and release from hRBCs.…”
Section: Red Light Stimulates the Release Of Dex From Rbcsmentioning
confidence: 99%